2002
DOI: 10.1128/aem.68.11.5387-5393.2002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of UV Irradiation in Inactivating Cryptosporidium parvum Oocysts

Abstract: To evaluate the effectiveness of UV irradiation in inactivating Cryptosporidium parvum oocysts, the animal infectivities and excystation abilities of oocysts that had been exposed to various UV doses were determined. Infectivity decreased exponentially as the UV dose increased, and the required dose for a 2-log 10 reduction in infectivity (99% inactivation) was approximately 1.0 mWs/cm 2 at 20°C. However, C. parvum oocysts exhibited high resistance to UV irradiation, requiring an extremely high dose of 230 mWs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 28 publications
(26 reference statements)
4
69
0
3
Order By: Relevance
“…Depuration using UV light is usually effective provided that the water flow rate is adequate to its capacity [15]. UV disinfection technology can be readily applied, is low maintenance, results in significant viability reductions of all waterborne pathogens, and produces no hazardous by-products [16,17]. UV radiation eliminates enteric bacteria, viruses, bacterial and protozoan spores in the water without the production of toxic by-products or other chemical residues [13].…”
Section: Introductionmentioning
confidence: 99%
“…Depuration using UV light is usually effective provided that the water flow rate is adequate to its capacity [15]. UV disinfection technology can be readily applied, is low maintenance, results in significant viability reductions of all waterborne pathogens, and produces no hazardous by-products [16,17]. UV radiation eliminates enteric bacteria, viruses, bacterial and protozoan spores in the water without the production of toxic by-products or other chemical residues [13].…”
Section: Introductionmentioning
confidence: 99%
“…While chlorine is the most common disinfectant in the United States for drinking water and wastewater treatment, alternative disinfectants are needed to reduce highly chlorine resistant pathogens, such as Cryptosporidium parvum. UV light disinfection is effective at reducing Cryptosporidium oocysts (6,34), and it is therefore an attractive alternative disinfectant to chlorine for drinking water treatment. Recent evidence, however, has shown that UV light is ineffective at reducing enteric adenovirus at doses commonly applied by water treatment systems (45).…”
mentioning
confidence: 99%
“…The molecular lengths of fragmented DNA are determined by alkaline agarose gel electrophoresis, followed by a theoretical calculation to obtain the number of ESS (14). This assay was applied in the survey of UV-irradiated health-related microbes such as Escherichia coli, Cryptosporidium parvum and Legionella pneumophila (15,16,17,18). The conditions for the ESS assay used in this study were basically the same as those described previously (15).…”
Section: Cell Numbermentioning
confidence: 99%